MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI BANGUN DATAR PERSEGI DAN PERSEGI PANJANG KELAS VII-2 MTSN BINJAI T. A. 2016/2017 - Asnil Aidah Ritonga (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
This type of research is a classroom action research. The purpose of the research is 1) To know how the communication ability of students before applied mathematics jigsaw type cooperative learning. 2) Describe the students' mathematical communication skills after implementing jigsaw type cooperative learning. 3) To know whether there is improvement of students' mathematical communication ability after doing jigsaw type cooperative learning. The study was conducted in two cycles with the subjects of all students of class VII-2 MTs Negeri Binjai which amounted to 40 students. To obtain data in this research used post test, observation sheet of student mathematics communication, interview and documentation. After the data collected and analyzed it is obtained: 1) The result of the initial ability of students' mathematics communication through the post test obtained 31 students or 77.50% of learning completeness level did not reach KKM (≥ 75), while only 9 students or 22.50 % Of learning completeness level reached KKM (≥ 75). 2) The improvement of students' mathematical communication ability is seen from the percentage of learning result that is on the pre cycle of 22,50%, increase in cycle I become 67,50%, and in cycle II increase to 87,50%. 3) The result of observation of student mathematics communication in cycle I obtained 51,12% with "Good" criteria, and increase in cycle II with percentage 71,16% with "Very Good" criteria. Based on the results of this classroom action research it can be concluded that the application of cooperative learning model jigsaw type can improve students' mathematical communication skills on square and rectangular building materials in class VII-2 MTs Negeri Binjai T.A. 2016/2017.